Association Between Acute Stroke and Metabolic Syndrome - Iqbal, Md Jabed; Siddiqui, Md Mahmudur Rahman; Islam, Quazi Tarikul; Hossain, Ahmed; Mustafa, Ekramul; Shipa, Md Ruhul Amin; Rahman, Md Yousuf Ur; Sina, Hashmi (Journal of Medicine, 2010)
Objective: Metabolic syndrome is the cluster of vascular risk factors including insulin resistance, elevated blood pressure, hyperlipidemia, and obesity. Metabolic syndrome is strongly associated with cardiovascular and cerebrovascular disease. The aim of this study is to find out association between stroke and metabolic syndrome in our population. Methods: In this observational study, a total number of fifty randomly selected patients were studied from July 2009 to December 2009 at Medicine ward of Dhaka Medical College Hospital. Definition of metabolic syndrome was taken from the guidelines by the National Cholesterol Education Program Adult Treatment Panel III. Results: Among the study population 46% had metabolic syndrome. This study estimated that Ischaemic stroke is more common among metabolic syndrome patients (65.2%), but patient without metabolic syndrome had more haemorrhagic stroke (55.6%).Only 12% patient was found obese. With or without metabolic syndrome most of the patient had elevated TG (64%) and raised blood pressure (64%). Conclusion: Without obesity, metabolic syndrome is an important risk factor for cerebrovascular disease. Majority of the patients with metabolic syndrome present as ischemic stroke. Keywords: Stroke; Metabolic syndrome; hypertension; fasting blood sugar; hyperlipidaemia. DOI: 10.3329/jom.v11i2.5453 J MEDICINE 2010; 11 : 124-127